5'-Untranslated sequences of two structural genes in the qa gene cluster of Neurospora crassa. - Alton, N K (1982)
The coding regions of two genes (qa-2 and qa-3) in the qa gene cluster of Neurospora crassa have been localized by nucleotide sequence analysis combined with data on previously determined NH2-terminal amino acid sequences for the proteins that these genes encode. The start point of transcription for each of these genes has been determined by nuclease S1 mapping experiments with poly(A)+RNA isolated from quinic acid-induced cultures of N. crassa. The sequences of approximately 200 nucleotides 5' to the start point of transcription have been compared with each other and with those of other eukaryotes. The results show that neither of these regions for the qa-2 nor the qa-3 genes share any significant homology with sequences apparently conserved in higher eukaryotic promoters (-25 and -70 regions). However, the qa-2 and qa-3 sequences do show homology with each other in these regions. Comparison of the 5'-flanking regions of these Neurospora genes with those of several Saccharomyces cerevisiae genes reveals a number of similarities in the region preceding the translation initiation codons.